2012
DOI: 10.1039/c2sm26441b
|View full text |Cite
|
Sign up to set email alerts
|

Formation of ring-shaped assembly of microtubules with a narrow size distribution at an air–buffer interface

Abstract: Biopolymers such as actin, microtubules and DNA are well known for their fascinating in vivo selforganization phenomena. Considerable efforts have been devoted to mimicking their organization process in vitro that produced ring-shaped or toroid structures in an irreversible manner. However, understanding the factors that lead to formation of such assembled structures deserves more investigation to achieve a unified insight into the assembly process, particularly of the microtubules. Here, we report an active a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Abbreviations: CW, clockwise; CCW, counter-clockwise; polym, polymerisation; SA, streptavidin; tub, tubulin. References: (1) [126], (2) [134], (3) [138], (4) [137], (5) [130], (6) [135], (7) [136], (8) [414], (9) [133], (10) [132], (11) [415], (12) [121]. Note that a number of mathematical models were put forward to describe loop or spool dynamics in gliding assays [141, 156, 157, 414, 416, 417]experimental conditionsdiameters of curvature [μm] a commentsref.kinesin-1 carpets standard tub, 10-20 μm taxol (after?)…”
Section: Understanding the Unusual Curling Behaviours Of Mts In Axonsmentioning
confidence: 99%
See 1 more Smart Citation
“…Abbreviations: CW, clockwise; CCW, counter-clockwise; polym, polymerisation; SA, streptavidin; tub, tubulin. References: (1) [126], (2) [134], (3) [138], (4) [137], (5) [130], (6) [135], (7) [136], (8) [414], (9) [133], (10) [132], (11) [415], (12) [121]. Note that a number of mathematical models were put forward to describe loop or spool dynamics in gliding assays [141, 156, 157, 414, 416, 417]experimental conditionsdiameters of curvature [μm] a commentsref.kinesin-1 carpets standard tub, 10-20 μm taxol (after?)…”
Section: Understanding the Unusual Curling Behaviours Of Mts In Axonsmentioning
confidence: 99%
“…Furthermore, exposure to non-polar interfaces (e.g. n-heptane or air bubbles) induces strong curling [138], and this may be relevant in axons: changes in physical and chemical parameters of neurons upon ageing or in degenerative diseases promote liquid-liquid phase separation [139]; liquid compartments likely are of low polarity [140] and might therefore influence the curling bias of MTs. All these parameters observed in vitro can be expected to apply also in axons and might contribute to the observed curling behaviours (Fig.…”
Section: Understanding the Unusual Curling Behaviours Of Mts In Axonsmentioning
confidence: 99%
“…In cooperation with bound molecular motors which can convert chemical energy into mechanical motion, filaments and microtubules play key roles in many cell functions, such as cargo transportation and mitosis. 1 In vitro experiments showed that, from motility assays, microtubules can self-organize into a lattice of nematic vortices 2–4 and microfilaments can self-assemble into clusters, swirls and bands. 5 Besides the bio-polymeric active matter, chains of synthetic self-propelled colloidal particles have already been realized in experiments, 6,7 which may potentially serve as a more flexible and controllable model system for studying the collective behavior of active polymers (APs).…”
Section: Introductionmentioning
confidence: 99%
“…Because kinesin is a protein and is relatively fragile as a material for machines, nanotools built with kinesins are designed to be disposed of, although a technique to lengthen the life of kinesins by oxygen scavenging has been reported. 21) Thus, we became motivated to realize regeneration of the active surface by reloading fresh kinesins to the surface. In this study, we attempted to remove the adsorbed kinesins by using a multi-photon laser ablation technique and to reload additional kinesins onto the treated area.…”
Section: Introductionmentioning
confidence: 99%